Impact of Thermal, High-Pressure, and Pulsed Electric Field Treatments on the Stability and Antioxidant Activity of Phenolic-Rich Apple Pomace Extracts - Diana Plamada; Miriam Arlt; Daniel Güterbock; Robert Sevenich; Clemens Kanzler; Susanne Neugart; Dan C. Vodnar; Helena Kieserling; Sascha Rohn (Molecules)
Apple pomace, a by-product of apple juice production, is typically discarded as waste. Recent approaches have focused on utilizing apple pomace by extracting beneficial bioactive compounds, such as antioxidant phenolic compounds (PCs). Before these PC-rich extracts can be used in food products, they must undergo food preservation and processing methods. However, the effects of these processes on the composition, stability, and properties of the PC remain insufficiently understood. The present study aimed at investigating the effects of a thermal treatment (TT), a high-pressure thermal treatment (HPTT), and a pulsed electric field treatment (PEF) on the composition and antioxidant activity of PC-rich apple pomace extracts (APEs). Major PCs, including phloridzin, chlorogenic acid, and epicatechin, as well as minor compounds, were identified by liquid chromatography–tandem mass spectrometry (LC-MS/MS) and high-performance thin-layer chromatography (HPTLC). As a stability indicative property, the antioxidant activity was analyzed by a Trolox equivalent antioxidant capacity assay (TEAC), electron paramagnetic resonance spectroscopy, and the Folin–Ciocalteu reagent assay. The results showed that TT at 80 °C increased phloridzin content, likely due to the hydrolysis of bound forms, while higher temperatures and HPTT resulted in a substantial PC conversion. The PEF treatment also caused notable PC conversion, but generally, it had a milder effect compared to TT and HPTT. Hence, low temperatures with and without high pressure and PEF seem to be the most promising treatments for preserving the highest content of major PC in APE. Antioxidant activity varied among the analytical methods, with HPTT showing minor changes despite PC loss compared to the untreated APE. This suggests that other antioxidant compounds in the extracts may contribute to the overall antioxidant activity. This study demonstrates that apple pomace contains valuable PC, highlighting its potential as a health-promoting food additive and the impact of conventional preservation and processing methods on PC stability.